Asymmetric Reduction of (R)‐Carvone through a Thermostable and Organic‐Solvent‐Tolerant Ene‐Reductase - Tischler, Dirk (Chembiochem, 2020)
Ene‐reductases allow regio‐ and stereoselective reduction of activated C=C double bonds at the expense of nicotinamide adenine dinucleotide cofactors [NAD(P)H]. Biological NAD(P)H can be replaced by synthetic mimics to facilitate enzyme screening and process optimization. The ene‐reductase FOYE‐1, originating from an acidophilic iron oxidizer, has been described as a promising candidate and is now being explored for applied biocatalysis. Biological and synthetic nicotinamide cofactors were evaluated to fuel FOYE‐1 to produce valuable compounds. A maximum activity of (319.7±3.2) U mg(−1) with NADPH or of (206.7±3.4) U mg(−1) with 1‐benzyl‐1,4‐dihydronicotinamide (BNAH) for the reduction of N‐methylmaleimide was observed at 30 °C. Notably, BNAH was found to be a promising reductant but exhibits poor solubility in water. Different organic solvents were therefore assayed: FOYE‐1 showed excellent performance in most systems with up to 20 vol% solvent and at temperatures up to 40 °C. Purification and application strategies were evaluated on a small scale to optimize the process. Finally, a 200 mL biotransformation of 750 mg (R)‐carvone afforded 495 mg of (2R,5R)‐dihydrocarvone (>95 % ee), demonstrating the simplicity of handling and application of FOYE‐1.